THE INFLUENCE OF ORGANIZATIONAL CULTURE, ABILITY, AND WORK MOTIVATION ON KINDERGARTEN TEACHERS' COMMITMENT IN ACEH TAMIANG REGENCY - Suriyani; Sari Rizki; Hera Yanti (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
This study aims to: (1) analyze the influence of organizational culture on the work motivation of kindergarten teachers in Aceh Tamiang Regency; (2) analyze the influence of ability on the work motivation of kindergarten teachers in Aceh Tamiang Regency; (3) analyze the influence of organizational culture on the commitment of kindergarten teachers in Aceh Tamiang Regency; (4) analyze the influence of ability on the commitment of kindergarten teachers in Aceh Tamiang Regency; (5) analyze the influence of work motivation on the commitment of kindergarten teachers in Aceh Tamiang Regency; and (6) analyze the influence of organizational culture, ability, and work motivation on the commitment of kindergarten teachers in Aceh Tamiang Regency. This study employs a quantitative approach with an associative research design. The population consists of 617 kindergarten teachers, with a sample of 243 teachers selected proportionally using the Slovin formula and random sampling technique. The results show that (1) there is a positive and significant influence between organizational culture and teachers’ work motivation; (2) ability and teachers’ work motivation; (3) organizational culture and teachers’ commitment; (4) ability and teachers’ commitment; and (5) work motivation and teachers’ commitment. All of these relationships are statistically significant with significance values below 0.05. (6) Simultaneously, organizational culture, ability, and work motivation contribute very significantly to teachers’ commitment, with a coefficient of determination (R²) of 0.998 or 99.8%. Based on the research findings, it is recommended that schools and education policymakers continuously strengthen positive organizational culture, enhance teachers’ ability through training and professional development, and create a work environment that fosters work motivation. Strengthening these three aspects has been proven to play an important role in improving teachers’ commitment on a ustainable basis.